Participatory survey on breastfeeding in marginalized Roma communities for practice - Hrustič, Tatiana; Poloková, Andrea (Romano džaniben, 2018)
The aim of this study is to present data and information from a participatory survey that preceded the setting up of health mediation activities in marginalized Roma communities and trainings of specialized lactation consultants to support breastfeeding in these communities. In the breastfeeding survey, 1306 questionnaires from different Romani communities in Slovakia and 787 questionnaires sent via an online form from non-Roma women receiving assistance from lactation consultants were processed. The article not only analyses the results of these participatory surveys, but also describes the experiences of the Roma health mediators who were involved in data collection in their localities and presents the use of the results in practice.
Keywords: Marginalized Roma Communities; lactation consultants; breastfeeding; health mediators; MAMILA; Zdravé regióny